(untitled) (Czech Journal of International Relations, 2025)
Poland’s response to the escalation of the Israeli-Palestinian conf lict after October 7th, 2023, showed considerable continuity, though notable signs of change were also evident. Among the key transformative variables, one can point out: the post-election government change and the consequent realignment with the EU-Brussels stance, and the reorienting public attitudes due to the dramatically deteriorating humanitarian crisis in Gaza that were accompanied by new social phenomena as pro-Palestinian street protests and campus campaigns. The paper aims to provide a deeper understanding of the dynamics of continuity and change in Poland’s relations with Israel and its stance on the Israeli-Palestinian conf lict. This paper argues that the interplay of international developments and domestic circumstances has led Poland to distance itself from Israel. If this trend becomes a harmonized and institutionalized foreign policy approach, it may ultimately redefine the Poland-Israel relations. Against this backdrop, the paper examines key drivers of this shift and its potential short- and medium-term consequences.